(untitled) (PesquisAtor, 2012)
This paper analyzes the features of the solo performance by Denise Stoklos in her concept of the “Essential Theater”. Investigates and organizes the processes of performance of the “essential performer” by means of desk research, interviews and some performances by actress. It suggests that this process from the performance imbricates with daily life, and leads the actor to be in a state of self-perception, capturing the elements which will be part of the dramatic and articulating both body and voice to stimulate the spectator to differentiated perceptions.